2017
DOI: 10.1055/s-0037-1599053
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Initiative for Critical Congenital Heart Disease Newborn Screening in Texas Neonatal Intensive Care Units

Abstract: The objective of this study was to implement a strategy for critical congenital heart disease (CCHD) newborn screening in the neonatal intensive care unit (NICU). A NICU-specific curriculum, screening algorithm, slide presentations, and templates of orders, policies, and procedures were developed into a toolkit for training NICU personnel. Screening was conducted on first and second screen pre- and postductal oxygen saturations (SpO) on newborns admitted or transferred to the NICU. We trained 347 NICU personne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…Use of the timed 25-foot walk test increased from 25 to 46% ( p < .001), use of clinic questionnaire for spasticity improved from 3 to 9% ( p < .001). Use of behavioral modifications, pharmacotherapy, and physical therapy remained unchanged Patients : NRGuillory 2017 [66]USNewborn screeningHospitals# hospitals: 13# providers: 117 physicians, hospital administrators, and other health care professionals, 215 nurses# patients: 11322Pre-postCritical Congenital Heart Deiseas (CCHD) Toolkit Implementation : PP presentation for physicians, PP presentation for nurses, sample nursery policy, Taryn's Story (4 minute video script), Lifesaving Newborn Screen (30 s PSA script) Provider : Algorithm card, sample physician order, sample screening log, wall poster for newborn nursery Patient : Brochure (English/Spanish) for positive screen, brochure (English/Spanish) for families Other intervention : A hospital nurse champion (HNC) was identified for each facility to serve as a leader, with responsibilities of training personnel, facilitating implementation, and identifying and addressing barriers. Nurse educators and HNCs conducted an accredited, 1-hour training session at each hospital to ensure standardization of education for the newborn nursing staff. Uptake : NR Feasibility : NR Providers : The pretest average was 71% and improved to 92.5% ( p < .0001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Use of the timed 25-foot walk test increased from 25 to 46% ( p < .001), use of clinic questionnaire for spasticity improved from 3 to 9% ( p < .001). Use of behavioral modifications, pharmacotherapy, and physical therapy remained unchanged Patients : NRGuillory 2017 [66]USNewborn screeningHospitals# hospitals: 13# providers: 117 physicians, hospital administrators, and other health care professionals, 215 nurses# patients: 11322Pre-postCritical Congenital Heart Deiseas (CCHD) Toolkit Implementation : PP presentation for physicians, PP presentation for nurses, sample nursery policy, Taryn's Story (4 minute video script), Lifesaving Newborn Screen (30 s PSA script) Provider : Algorithm card, sample physician order, sample screening log, wall poster for newborn nursery Patient : Brochure (English/Spanish) for positive screen, brochure (English/Spanish) for families Other intervention : A hospital nurse champion (HNC) was identified for each facility to serve as a leader, with responsibilities of training personnel, facilitating implementation, and identifying and addressing barriers. Nurse educators and HNCs conducted an accredited, 1-hour training session at each hospital to ensure standardization of education for the newborn nursing staff. Uptake : NR Feasibility : NR Providers : The pretest average was 71% and improved to 92.5% ( p < .0001).…”
Section: Resultsmentioning
confidence: 99%
“…Studies did not separate effects of toolkits versus other intervention elements when these were present. With some exceptions [18, 21, 26, 32, 34, 43, 48, 50, 60, 63, 65, 66, 68, 70, 73, 76, 78, 88], provider effects were studied using post only designs such as asking providers to describe the effects of the toolkit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one Texas multi-institution study, between 46.3% and 80% of infants were missed depending on screening characteristics of the infant (with the most premature group of less than 28 weeks being the least protocol compliant). 17 An NICU-specific multicenter collaborative found that the number of infants not screened according to the protocol was approximately 1.1%. 18…”
Section: Discussionmentioning
confidence: 99%